Direction Of Soil Conservation As A Way Of Conserving The Capability Of The Environment - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
ABSTRACT This paper is part of the research conducted in Sedayu district, Bantu( Regency Yogyakarta Special Region, Indonesia. The aim was to classy soil erosion hazard in the area, construct land capability classes and establish some of the social-economic factors that influence farmers in implementing soil conservation activities. Survey method and purposive stratified techniques of sampling were used Social-economic factors were quantified using scoring and later analysed using SPSS computer program. Results indicated that the dominant land capability class in the area was class I found on land units consisting of alluvial plains with slope steepness 1% - 3% and having wet rice as land use (F.IR) and land unit consisting of alluvial plain, slope steepness between I% - 3% and having mixed gardening as a major land use (F1.14 They had a very low degree of erosion hazard. Land units with mixed gardening as a major land use and found on karst landforms with slope steepness ranging between 8% -15% were identified as having a very high degree of soil erosion hazard (K2.111.10. The dominant land capability classes were I, II, and III, while classes VII and VIII were limited to a small area. Among the social-economic factors, it was found out that the education factor had the greatest influence towards the farmer's response to conservation activities in the research area.